Analisis Framing Media BBC NEWS dan Detik NEWS terhadap Pemberitaan Cina Mengubah Ratusan Nama Desa di Xinjiang untuk Menghapus Budaya Muslim Uighur - Putri Alham, Rana Dwi (Universitas Syiah Kuala, 2025)
This article explores how BBC News and Detik News frame reports on the Chinese governments renaming of hundreds of villages in Xinjiang, viewed as an attempt to erase Uyghur Muslim culture, and examines Chinas stance toward the Uyghur ethnic group. The study aims to reveal how media construct reality through a framing approach. This qualitative research uses a literature review method, collecting data from books, academic journals, and online sources. The framing analysis applies Robert N. Entmans model, which includes four components: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Findings show that both media refer to Human Rights Watch reports and highlight human rights violations. BBC News presents a more balanced perspective, while Detik News emphasizes violence and advocacy. The Chinese governments stance is driven by political and national security interests, leading to counter-terrorism policies.Keywords: Framing; Online Media; Human Rights; Uyghur